Avaliação de um novo sistema de dosimetria por luminescência opticamente estimulada - Barros, Cássia Eugênia (2023)
This work aims to establish a dosimetric system composed of an optically stimulated luminescence reader - developed in Brazil and called LumiDeteck 3000 - with dosimeters of 3 different materials- BeO, CaSO4:Dy, and Al2O3:C. The dosimeters were separated into groups irradiated with a linear accelerator for doses of a few Gy and an X-Ray tube for Doses of a few mGy. The luminescence curve was generated by the reader for each dosimeter, from which the luminescence integral - expected to be proportional to the dose - was calculated. The reading of some groups of dosimeters was compared with readings taken on a commercial reader, the Lexsyg Smart reader. Tests were carried out to evaluate the dependence of the result of the readings on temperature. The linear relationship between the luminescence integral and the expected irradiated dose of LOE readers was observed, however, the results showed that the LOE curves for doses below 0.5 Gy present a noise level sufficient to impair the reliability of the reading, which does not happen with the Lexsyg Smart. Measurements made as a function of temperature indicate that noise decreases significantly with temperature, showing that a cooling system possibly enables reliable reading of doses of mGy. More tests should be carried out, and a room with a better cooling system should be used.